An investigation of practices taken by corporations in the hospitality industry toward creating a more sustainable future - Raffaut, Nicolette Vaidarlis (The IIE, 2020)
The study aimed to gain insight on what employees at The OBH Group understand environmentally friendly practices to be and how they are carried out in order to be considered a green hotel; and to work toward achieving their sustainable development goals by 2030. It also aims to discover the effects, if any, that COVID-19 has had on implementing these practices. Following a qualitative approach to explore, understand, describe and obtain deeper insight from employees at the chosen hotel, semi-structured interviews were conducted on four participants. As described by all four participants, implementation of green practices is important to the hotel in order to reduce the overall carbon footprint and to be cost-effective in the long run. It is also important for the hotel to implement these practices as guests are becoming more eco-conscious and look for that when traveling. As interpreted from the findings, COVID-19 has delayed the implementation of some practices and has resulted in the need to utilize single-use plastics for health and safety reasons, and has also resulted in seeking alternate and new suppliers. However, there are green practices that are in place that makes the hotel on that is environmentally-friendly.
Keywords: Sustainability; SDG 2030; Green practice; Carbon footprint; Eco-conscious; COVID-19; Cost-effective